Liveworksheets E-LKPD Development for Nahwu Learning: Pengembangan Lembar Kerja Interaktif E-LKPD untuk Pembelajaran Nahwu - Rizki Amirul Huda; Khizanatul Hikmah (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The integration of educational technology in the 21st century requires innovative digital learning media to support effective classroom practices. Specific Background: In Arabic language instruction, particularly Nahwu learning for Grade X students, limited interactive media has contributed to low engagement and understanding. Knowledge Gap: Conventional textbook-based approaches have not adequately facilitated active participation and interactive learning experiences in Nahwu instruction. Aims: This study aims to develop a Liveworksheets-based electronic student worksheet (E-LKPD), named ELIWO, and to examine students’ responses to its implementation. Results: Using a Research and Development approach with the ADDIE model, the product was validated by subject matter experts (97%) and media experts (96%), indicating very high validity. A limited trial involving 40 students at SMA Muhammadiyah 2 Sidoarjo yielded a positive response with an average score of 4.00 (80%), categorized as good. Novelty: The study presents a structured development of an interactive Liveworksheets-based E-LKPD specifically designed for Nahwu learning at the senior high school level. Implications: The findings indicate that ELIWO is feasible and practical as a digital learning medium to support structured Nahwu instruction. Keywords: E-LKPD, Liveworksheets, Nahwu Learning, ADDIE Model, Educational Technology Key Findings Highlights: Expert validation indicated very high product feasibility levels. Student trial demonstrated positive acceptance in classroom use. The developed digital worksheet supports structured grammar instruction.